Why Citizens Participate in Local Governance: A Case of Two Philippine LGUs. Issue 12 (14th October 2016) - Caparas, Maria Veronica G.; Agrawal, Anand
ABSTRACT: The well-established importance of citizen participation in local and community governance raises a number of problems, foremost of which has been the reduced level of citizens' involvement and engagement in developing countries. Our study aims at exploring the factors that impact citizen participation in two local government units (LGUs) in the Philippines. We propose the models of LGU participation and regular attendance in meetings based on the regression results of our study and present policy implications and insights essential in designing strategies for a higher level of LGU constituents' attendance in meetings and participation in local governance matters.